Analisis Kualitas Jaringan Internet Wireless LAN PT. Teladan Prima Agro - Ahmad Ridhani Mubaraq; Naufal Azmi Verdikha; Muhammad Taufiq Sumadi (Lembaga Pengembangan Kinerja Dosen, 2024)
The internet or interconnected networking is a network that connects computers of various types that form a network system that covers the entire world. This research aims to determine the quality of the internet network of PT Teladan Prima Agro (PT TPA). The research method used is Quality Of Service (QoS) with data retrieval techniques using Wireshark software. The results showed that the average QoS index of the PT. TPA office internet network based on the TIPHON standard obtained the result